Design and Implementation of An Efficient Information System for Broiler Chicken Rearing: A Case Analysis VR Broiler Farm - Kusumawati, Marhani Wiji Ayu; Fachrie, Muhammad (International Journal Software Engineering and Computer Science (IJSECS), 2023)
With the rapid advancements in information technology, there is a corresponding increase in the competitiveness of business enterprises. In this context, the utilization of computerized business management administration is recommended to streamline business operations, thereby enhancing efficiency and effectiveness, ultimately leading to increased profitability. VR Broiler Farm, a specialized broiler chicken farming business, currently records its broiler chicken maintenance data manually. This practice, stemming from a lack of utilization of contemporary technology, leads to longer data recording processes and potential data inconsistencies. Given this scenario, there is a clear need for an information system tailored for poultry farmers to facilitate faster and more efficient data recording. This system would cover various aspects including scheduling identification, chicken feed requirements, mortality rates, total chicken count, and other data relevant to broiler chicken farming. Therefore, the implementation of an information system for managing broiler chicken farming can provide valuable insights into the developmental trends of broiler chicken production.